(دور المدرسة في تعزيز قيم المواطنة الرقمية لدى الطلبة) (Comprehensive Journal of Science, 2026)
The rapid transformation towards a digital environment has made digital citizenship values an essential requirement for ensuring the safe and effective use of modern technologies. The school, as the primary educational institution, plays a central role in instilling these values and guiding students toward responsible digital behavior. This paper aims to highlight the role of schools in promoting students’ awareness of digital citizenship by integrating it into curricula, organizing awareness activities, and strengthening collaboration between teachers and parents. It also emphasizes the importance of equipping teachers with digital and pedagogical skills that support respect for digital rights, protection of privacy, and the prevention of negative behaviors in the online space. The study concludes that schools are a key foundation in preparing a generation capable of engaging with the digital age with awareness and responsibility, thereby contributing to the development of a sustainable knowledge society.
Keywords: Digital Citizenship – School – Values – Students – Educational Technology – Digital Awareness – Socialization – Online Behavior.